Sexual Dysfunction in Women and Men with Psoriasis: A Cross-Sectional Questionnaire-Based Study - Kamila Kędra; Kinga Janeczko; Izabela Michalik; Adam Reich (Medicina, 2022)
Background and objectives: Psoriasis can lead to feelings of stigmatization, hinder social functioning, and impair quality of life. Psoriasis can also affect sexual activity, but there is still little research on this topic. The present study investigated whether and to what extent psoriasis, its severity, location and extent of skin lesions affect sexual dysfunction. Materials and Methods: A total of 45 women and 64 men aged 18 to 73 years hospitalized for psoriasis exacerbations were included in the study. Psoriasis severity, as assessed by the Psoriasis Area and Severity Index (PASI), ranged from 0.2 to 65 points (mean: 17.0 ± 14.9 points). After collecting demographic and clinical data, each subject was asked to complete the Dermatology Life Quality Index, the 11-item Sexual Life Questionnaire and the International Index of Erectile Function (only men). Results: Our study found that more than 90% of the patients surveyed felt at least a slight unattractiveness due to psoriasis. In approximately 80% of the subjects, the skin lesions at least occasionally affected their sex life, and more than 50% at least sometimes avoided sexual contact. The location of psoriasis, particularly in the genital area (p = 0.01), on the face (p = 0.03) and hands (p = 0.05), also had a significant impact on the level of sexual problems. Psoriasis has a significant impact on the quality of life (QoL), and a deterioration in QoL was strongly correlated with sexual dysfunction (r = 0.6, p < 0.001), PASI scores (r = 0.36, p < 0.001), self-assessment of psoriasis severity and location of psoriatic lesions. Conclusions: Psoriasis leads to various limitations, especially in the sphere of sexual life. Patients with psoriasis feel stigmatized, have lowered self-esteem and consequently experience significant sexual problems. Awareness of the co-occurring psychological aspect of psoriasis and the routine use of validated scales in dermatology practice should contribute to the rapid identification of patients with sexual dysfunction.